Acute Aorto-Illiac Occlusion with Bilateral Limb Ischemia Underwent Direct Catheter Thrombolysis in Older Patient: A Case Report - Irma Kamelia; Novi Kurnianingsih (Universitas Brawijaya, 2021)
BACKGROUND: Peripheral arterial diseases could be a major burden for the health system with a wide clinical spectrum from symptomatic to the limb threatening. A sudden onset of limb deteriorations represent a vascular emergency and need a proper treatment to limb preservation and life-saving. It is still challenging to choose a proper management to reduce morbidity and mortality, despite a various advance of diagnostic and therapeutic tools were available.CASE SUMMARY: A 70-years-old man came to our hospital with chief complaint leg pain at both of his legs, suddenly since 18 hours before admission. He had parasthesia and paralysis in both of his legs. And the doppler ultrasonography result was occlusion proximal to the right and left common iliac artery. Then we performed percutaneous intra-arterial thrombolysis using streptokinase and had gastrointenstinal bleeding as an adverse event.DISCUSSION: This case report provides an example of management acute limb ischemia in developing country with a limited source in comparison with the recent guideline and study. Further research is needed to establish a proper management to reduce morbidity and mortality in these cases.